QIRIAH SIZMIYIIYAH FIZ AL-QISHSHAH AL-QURANIYAH ASHHAB AL-SABT - Chabi, Souad (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2017)
The semantic approach is one of the contemporary cretic approaches It reads text In second reading; By analyzing its meaning; Focus on both linguistic and non-linguistic signs; Such as space, time, human or animal characters, scenes and other elements of a text. So we tried to apply this reading on the story of the Quranic its story of the owners of the Saturday, and chose the title of our research,